Azathioprine‐induced Sweet's syndrome: A case series and review of the literature. (24th August 2015) - McNally, Ashling; Ibbetson, Jan; Sidhu, Shireen
Abstract: We present three patients with azathioprine‐induced Sweet's syndrome (AISS) who attended our tertiary institution within a 12‐month period. Established associations exist between Sweet's syndrome and some medications; however, to date links to azathioprine are tentative. While there are case reports of AISS, most have occurred in patients with inflammatory bowel disease (IBD), an underlying predisposition for Sweet's syndrome. Our case series adds to the evidence that the entity of AISS truly exists independent of confounding factors such as concurrent IBD.